PSVII-21 The impact of cell culture and copper dose on copper trafficking genes in bovine liver - Tillquist, Nicole M (J Anim Sci, 2020)
The objective of the current experiment was to investigate the influence of Cu dose on the relative abundance of Cu trafficking genes in cultured bovine hepatocytes. A liver sample was obtained immediately post-mortem from one healthy Angus steer. Hepatocytes were isolated, counted, and seeded at equal density into 15 separate wells, and incubated for 1 hour in culture media containing: 0.0, 0.10, 1.0, 10.0, or 100 mg Cu/L (3 replicates per Cu dose). Following incubation, cells were collected and total RNA was isolated. Quantitative RT-PCR was used to determine the abundance of transcripts for proteins involved in Cu homeostasis. The identified targets were: ALDH2, APOA1, ATOX1, ATP7A, ATP7B, BHMT, BLVRB, CA2, CCS, COX17, CTR1, ELN, GAPDH, GLUD1, GSS, LOXL1, PDIA3, SOD1, SOD3. β-Actin (ACTB) served as the endogenous control. Significant linear responses existed for ALDH2 (P < 0.001), ATOX1 (P < 0.01), PDIA3 (P < 0.05). As Cu dose increased, the relative abundance of ALDH2 increased, and ATOX1 and PDIA3 decreased. Significant quadratic responses existed for ATP7B (P < 0.001), COX17 (P < 0.05), and SOD1 (P < 0.05). The relative abundance of COX17 was lesser at 0.1 and 1.0 mg Cu/L when compared to 0.0, 10, and 100 mg Cu/L. Transcript abundance for ATP7B and SOD1 was lower at 0, 1, and 100 mg Cu/L when compared to 0.1 and 10 mg Cu/L. These data indicate that certain transcripts are differentially expressed in cultured bovine hepatocytes in response to increasing Cu dose.